2022
DOI: 10.3390/diagnostics12081804
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Endobiliary Radiofrequency Ablation in Preserving Survival, Performance Status and Chemotherapy Eligibility of Patients with Unresectable Distal Cholangiocarcinoma: A Case-Control Study

Abstract: Background: Cholangiocarcinoma is the most common malignancy of the bile ducts causing intrahepatic, hilar, or distal bile duct obstruction. Most jaundiced patients are diagnosed with unresectable tumors in need for palliative bile duct drainage and chemotherapy. Endobiliary radiofrequency ablation (RFA) is an adjuvant technique that may be applied prior to biliary stenting. The aim of our study was to assess the efficacy of endobiliary RFA prior to stent insertion in patients with unresectable distal cholangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A recent RCT included 25 patients with histologically confirmed unresectable distal cholangiocarcinoma, and randomly divided them into the RFA group (n = 8) and the control group (n = 17). The results showed that patients who received intraductal RFA had prolonged average OS (19 months vs 16 months, P = 0.04), improved quality of life, and more significantly improved liver and kidney functions 31 . Recent meta‐analyses have also suggested that compared to stenting alone, endobiliary RFA combined with stent implantation can prolong patient survival and stent patency in MBS without increasing the incidence of adverse events 32–35 .…”
Section: Indications For Endobiliary Rfamentioning
confidence: 99%
“…A recent RCT included 25 patients with histologically confirmed unresectable distal cholangiocarcinoma, and randomly divided them into the RFA group (n = 8) and the control group (n = 17). The results showed that patients who received intraductal RFA had prolonged average OS (19 months vs 16 months, P = 0.04), improved quality of life, and more significantly improved liver and kidney functions 31 . Recent meta‐analyses have also suggested that compared to stenting alone, endobiliary RFA combined with stent implantation can prolong patient survival and stent patency in MBS without increasing the incidence of adverse events 32–35 .…”
Section: Indications For Endobiliary Rfamentioning
confidence: 99%
“…19 Metallic stents were inserted in five studies 20,[22][23][24]26 and plastic stents were inserted in six. [16][17][18][19]21,25 All the studies recorded survival time, in different forms, but the duration of stent patency was recorded in only seven of the studies. [16][17][18][19][20][21]26 Adverse events were recorded in nine studies.…”
Section: Baseline Characteristics and Assessment Of Studiesmentioning
confidence: 99%
“…After removing duplicates and irrelevant studies, 63 studies remained for the assessment of their full text for eligibility. Ultimately, 11 studies (4 RCTs [16][17][18][19] and 7 OSs [20][21][22][23][24][25][26] ) were found to be eligible for qualitative synthesis. The flow diagram of the selection process is shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumour progression can lead to decreased stent patency requiring stent replacement [ 81 ]. Several studies have shown prolonged stent patency with the use of local therapies, including intraluminal brachytherapy and radiofrequency ablation (both with and without chemotherapy), leading to improved outcomes in patients [ 82 , 83 , 84 , 85 ].…”
Section: Systemic Therapy For Unresectable Advanced or Metastatic Bil...mentioning
confidence: 99%